The teaching professional (de)valuation: implications of the supply and demand of teaching professionals in Paraná (2009-2013) (Práxis Educativa, 2017)
This paper aims at analyzing the relation between supply and demand of teaching professionals in the state of Paraná (2009-2013) by questioning the relation between work and education in capitalism, as well as the process of teaching professionals (de)valuation. The analysis was based on the historical-dialectical materialism theoretical-methodological approach, addressing the ontological conception of work and focusing on its capitalist historical dimension. The research surveyed statistical data from the National Institute of Studies and Education Research Anísio Teixeira (INEP, Brazilian Portuguese abbreviation), information given by the State of Paraná Education Secretariat (SEED-PR, Brazilian Portuguese abbreviation) and data made available by 37 Higher Education Institutions (IES, Brazilian Portuguese abbreviation) in the State of Paraná. The results revealed that there is greater supply of teaching professionals in relation to the job market demand for such activity, which leads to an excess of teachers. The conclusions reveal that this condition tends to contribute to the devaluation of this workforce. Keywords: Supply and demand of professionals. Teaching professionals. Workforce devaluation.